Denosumab for Management of Hypercalcemia in Primary Hyperparathyroidism - Zhao, Yihan; Zhang, Fang; Zhang, Simin; Zhang, Xiaona; Gao, Leili; Ren, Qian; Han, Xueyao; Ji, Linong (Hormone and Metabolic Research, 2024)
Denosumab is a completely human monoclonal high-affinity antibody that binds to the nuclear factor kappa-B ligand (RANKL) and is widely used to treat osteoporosis. Furthermore, it can potentially lower serum calcium levels by inhibiting osteoclast activation and preventing bone calcium from being released into the blood. This review aimed to provide evidence of the efficacy and safety of denosumab in treating hypercalcemia in primary hyperparathyroidism (PHPT). PubMed and the Cochrane Library were searched for published studies that described denosumab for hypercalcemia management in PHPT. Data were extracted by two independent investigators and analyzed using SPSS 23. The risk of bias was assessed by NIH Quality Assessment Tool. In total, 161 patients with PHPT from 18 studies were included in this review. The average age was 61 (47–72) years and the highest serum calcium was 3.76 (3.11–4.20) mmol/l. We found that denosumab can effectively reduce the serum calcium level by a median reduction of 0.5 mmol/l within 3 days. Significant reduction was maintained for 14 days. The serum calcium-lowering effect weakened after one month. In conclusion, denosumab has a potential clinical value in treating hypercalcemia in patients with PHPT.
Keywords: denosumab; calcium homeostasis; hypercalcemia; hyperparathyroidism